Strategic Planning of Information System in PT Satya Mitra Sejahtera Using Ward and Peppard - Reza Farid Azizi; Melkior Nikolar Ngalumsine Sitokdana (Politeknik Pertanian Negeri Samarinda, 2020)
Increasing demand in every company for information systems strategic planning in order to increase efficiency, effectiveness and increase competitive advantage programmatically with a priority scale, given the information system resources and other supporting devices are still limited, so the existence of an information system strategic plan will help the company. One of them is PT Satya Mitra Sejahtera, which is engaged in business, which is currently not fully using information systems to its full potential. The quality of information systems becomes the most important component because it requires an analysis of the strategic planning of information systems to determine whether the information system that was developed can be used properly. In this study, the author will conduct an information system strategic planning using the Ward and Peppard method. This method was chosen because it can evaluate business conditions and information systems that occur at this time, by looking at the business environment and information system environment externally and internally. The Ward and Peppard method have several stages, the first stage of analyzing the internal and external business environment using the PEST and value chain. Analysis of the internal and external environment of information systems using SWOT, while the application portfolio mapping uses Mc Farlan Strategic Grid. The results of strategic design research using Ward and Peppard methods can produce maps of internal and external conditions of the organization, so that can find out the strengths, weaknesses, opportunities, and threats owned by PT. Satya Mitra Sejahtera.